Monetary consequences of fiscal stress in a game theoretic framework - Dat Thanh Nguyen; Viet Anh Duong Hoang (Journal of Central Banking Theory and Practice, 2020)
This paper maps Leeper and Walker (2011) model into a game theory framework to study about the strategic aspects of monetary and fiscal interaction under a fiscal stress caused by an ageing population problem. The paper reveals that the outcomes of the game depend on the parameters of the underlying model, the size of the projected transfers and the public inflation expectation. The findings show that commitment to the target (inflation, government transfers) plays a crucial role in the policy interaction.
Keywords: E63; C70; 330; Monetary-fiscal interaction; Game theory; Ageing population; Dynamic leadership; Stochastic timing